RIEMANN-ROCH THEOREM FOR PLANE ALGEBRAIC CURVES OVER ALGEBRAICALLY CLOSED FIELD WITH ZERO CHARACTERISTIC - Siddiq Wira Awaldy, Muhammad
Abstract The Riemann-Roch’s theorem is a theorem that is very important in studying the structure of meromorphic functions on Riemann surfaces. One consequence of the Riemann-Roch’s theorem states that every compact Riemann surface can be viewed as an irreducible projective algebraic curve. In this thesis, we will present an exposition of the Riemann-Roch’s Theorem on algebraic projective curves over an algebraically closed field with zero characteristic.